The Intervening of Purchase Decision Between Marketing Mix, Consumer Behaviour and Brand Image on Costumer Statisfaction - Ramli S.; Abdul Rahman Mus; Hasanuddin Damis; Amir Mahmud (Jurnal Manajemen Bisnis, 2021)
The purpose of this study is to analyze the influence of the marketing mix, consumer behavior and brand image on consumer satisfaction through purchasing decisions of bottled water products in west Sulawesi province. A sample of 164 respondents where the sample withdrawal technique used accediantial sampling, a data collection instrument using questionnaires. Data analysis method uses structural equation model (SEM) with confirmatory factor analysis (CFA) AMOS 21.0 program. The results of the study prove that: 1) The marketing mix has a significant positive effect on purchasing decisions. 2) Consumer behavior has a significant positive effect on purchasing decisions. 3) The brand image has no significant positive effect on purchasing decisions. 4) The marketing mix has no significant positive effect on consumer satisfaction. 5) Consumer behavior has a significant positive effect on consumer satisfaction. 6) Brand image has a significant positive effect on consumer satisfaction. 7) Purchasing decisions have a significant positive effect on consumer satisfaction. 8) The marketing mix affects consumer satisfaction through purchasing decisions. 9) Consumer behavior affects consumer satisfaction through purchasing decisions.10) Brand image has no effect on consumer satisfaction through purchasing decisions.